(untitled) (The International Journal for Scientific Research, 2026)
This research aims to explore the role of unused structures in Ibn Jinni’s book "Al-Munsif" in teaching and developing the Arabic language. The researcher addressed the theoretical framework related to the role of unused structures in teaching Arabic, using Ibn Jinni’s "Al-Munsif." The descriptive-analytical method was employed, and the research sample consisted of secondary school students. Data was collected through questionnaires designed for this research. The researcher concluded that unused structures play a role in building the learner’s linguistic competence. Sound morphological rules can produce understandable forms even if they are not used. Furthermore, analogy is restricted by usage and linguistic convention, making the learner appreciate the beauty of linguistic choice. Unused structures can be used in teaching Arabic to enhance students’ understanding of classical texts and develop their language skills.